Cofactors of drug hypersensitivity—A monocenter retrospective analysis - Kühl, Johanna; Bergh, Björn; Laudes, Matthias; Szymczak, Silke; Heine, Guido (Frontiers in Allergy, 2023)
Background: Drug hypersensitivity reactions (DHR) are a major medical problem that influence the treatment of patients by both under- and overdiagnosis. Still, little is known about the role of predisposing or protecting cofactors of DHR. Objective: To determine drug-specific cofactors in patients with DHR. Methods: Retrospective file chart analysis between 2015-2020 from inpatients with suspected DHR in our department. Descriptive statistics and a multiple logistic regression model for the estimation and statistical interference. Results: DHR were suspected in 393 patients with 678 culprit drugs. In 183 cases drug hypersensitivities were confirmed, mostly against non-opioid analgesic drugs and antibiotics. Multiple logistic regression analysis identified a positive association of antibiotic hypersensitivity with obesity (OR 5.75, average marginal effect (AME) +24.4%), age and a negative with arterial hypertension, female sex, elevated IgE and allergic rhinitis. A hypersensitivity to non-opioid analgesics was associated with atopic dermatitis (OR 10.28, AME +28.5%), elevated IgE, and arterial hypertension. Conclusions: Drug-specific cofactors of DHR include obesity for antibiotics and atopic dermatitis for non-opioid analgesics, the knowledge of which may improve the risk calculation for drug provocation tests.